2021
DOI: 10.3389/fcell.2021.718991
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Assessment Model Based on Molecular Subtypes of Hypoxia-Related LncRNAs for Prognosis of Bladder Cancer

Abstract: Hypoxia is a common feature in various tumors that regulates aggressiveness. Previous studies have demonstrated that some dysregulated long non-coding RNAs (lncRNAs) are correlated with tumor progression, including bladder cancer (BCa). However, the prognostic effect of hypoxia-related lncRNAs (HRLs) and their clinical relevance, as well as their regulatory effect on the tumor immune microenvironment, are largely unknown in BCa. A co-expression analysis between hypoxia genes and lncRNA expression, which was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Due to the poor clinical value of classification into two clusters, we decided to construct a risk model same as previous studies (Chen et al, 2021c;Tang et al, 2021). According to the aforementioned prognostic NLRs and corresponding coefficient value, the risk score was calculated as follows: risk score = (0.9220 × HMGA2-AS1 expression) + (0.5187 × LINC02489 expression) + (−0.8027×ETV7-AS1 expression) + (0.2899 × EMSLR expression) + (−1.7005 × AC005954.1 expression) + (−0.5790 × STAG3L5P-PVRIG2P-PILRB expression) + (0.1412 × LINC02178 expression).…”
Section: Construction and Evaluation Of Prognostic Value Of Necroptos...mentioning
confidence: 99%
“…Due to the poor clinical value of classification into two clusters, we decided to construct a risk model same as previous studies (Chen et al, 2021c;Tang et al, 2021). According to the aforementioned prognostic NLRs and corresponding coefficient value, the risk score was calculated as follows: risk score = (0.9220 × HMGA2-AS1 expression) + (0.5187 × LINC02489 expression) + (−0.8027×ETV7-AS1 expression) + (0.2899 × EMSLR expression) + (−1.7005 × AC005954.1 expression) + (−0.5790 × STAG3L5P-PVRIG2P-PILRB expression) + (0.1412 × LINC02178 expression).…”
Section: Construction and Evaluation Of Prognostic Value Of Necroptos...mentioning
confidence: 99%
“…Bladder cancer (BCa) is a tumor growing in the mucosa of the bladder and is one of the most prevalent urogenital malignancies, ranking sixth among male-related cancers [ 1 ]. In today's clinical treatment, cystoscopy pathological biopsy is the gold standard for detecting this highly heterogeneous cancer [ 2 , 3 ]. BCa is categorized into two categories based on tumor invasion in the bladder: nonmuscle-invasive and muscle-invasive.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been revealed that targeting certain HRL can be an effective method in cancer treatment [10,12]. Recently, several studies have explored the possibility of developing a HRL signature to predict patients' survival and tumor microenvironment in multiple cancer types [14][15][16]. Nevertheless, application of the HRL signature in CRC is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lncRNA could upregulate the expression of HIF by increasing HIF-1α expression at both transcription and posttranscription levels [35]. Recently, a series of studies revealed that several hypoxia-related lncRNA signatures could provide predictive value [14,16,36]. In bladder cancer, a lncRNA signature consisting of 4 hypoxia-related lncRNAs was constructed and was found to exhibit excellent predictive performance [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation